2016
DOI: 10.1007/s12275-016-6526-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil pH and electrical conductivity are key edaphic factors shaping bacterial communities of greenhouse soils in Korea

Abstract: Soil microorganisms play an essential role in soil ecosystem processes such as organic matter decomposition, nutrient cycling, and plant nutrient availability. The land use for greenhouse cultivation has been increasing continuously, which involves an intensive input of agricultural materials to enhance productivity; however, relatively little is known about bacterial communities in greenhouse soils. To assess the effects of environmental factors on the soil bacterial diversity and community composition, a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
57
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(76 citation statements)
references
References 51 publications
14
57
1
4
Order By: Relevance
“…Soil EC has been used as a good indicator of soil stress level and is generally correlated with soil pH. In agreement with our findings, Kim et al [67] suggested that the bacterial community in intensively cultivated greenhouse soils could be particularly affected by soil pH and EC. Soil pH had also shown one of the most important environmental factors impacting bacterial abundance and diversity in natural and agricultural ecosystems [68].…”
Section: Discussionsupporting
confidence: 92%
“…Soil EC has been used as a good indicator of soil stress level and is generally correlated with soil pH. In agreement with our findings, Kim et al [67] suggested that the bacterial community in intensively cultivated greenhouse soils could be particularly affected by soil pH and EC. Soil pH had also shown one of the most important environmental factors impacting bacterial abundance and diversity in natural and agricultural ecosystems [68].…”
Section: Discussionsupporting
confidence: 92%
“…The change in fungal composition may be a result of both fertilization and the observed increase in hydrolysis N cycling (Thompson & Kao-Kniffin, 2019). Agricultural management practices, such as high fertilizer usage and restricted irrigation can immensely influence electrical conductivity variation (Adviento-Borbe et al, 2006;Kim et al, 2016). Electrical conductivity is associated with soil salinity and our results suggest it may be an important predictor of fungal community compositions in continuous cropping soils of A. macrocephala.…”
Section: Discussionmentioning
confidence: 60%
“…Bacteroidetes, Alphaproteobacteria and Betaproteobacteria were stimulated by wood ash application. Members of Bacteroidetes benefit from wood ash application (Noyce et al , 2016; Bang-Andreasen et al , 2017); they are initial metabolizers of labile carbon and respond positively to increased soil pH and electrical conductivity (Fierer et al , 2007; Lauber et al , 2009; Kim et al , 2016). Alpha- and Betaproteobacteria are also generally copiotrophic (Fierer et al , 2007; Cleveland et al , 2007); Betaproteobacteria thrive in soils with higher pH (Kim et al , 2016), whereas Alphaproteobacteria are favoured at high N availability (Nemergut et al , 2010; Fierer et al , 2012).…”
Section: Discussionmentioning
confidence: 99%